Aging behaviour of 25Cr-17Mn high nitrogen duplex stainless steel - Machado, I. F.; Padilha, A. F. (Iron Steel Inst Japan Keidanren Kaikan, 2000)
The precipitation behaviour of a nickel free stainless steel containing 25% chromium, 17% manganese and 0.54% nitrogen, with duplex ferritic-austenitic microstructure, was studied using several complementary techniques of microstructural analysis after aging heat treatments between 600 and 1 000 degrees C for periods of lime between 15 and 6 000 min. During aging heat treatments, ferrite was decomposed into sigma phase and austenite by a eutectoid reaction, like in the Fe-Cr-Ni duplex stainless steel. Chromium nitride precipitation occurred in austenite, which had a high nitrogen supersaturation. Some peculiar aspects were observed in this austenite during its phase transformations. Chromium nitride precipitation occurred discontinuously in a lamellar morphology, such as pearlite in carbon steels. This kind of precipitation is not an ordinary observation in duplex stainless steels and the high levels of nitrogen in austenite can induce this type of precipitation, which has not been previously reported in duplex stainless steels. After chromium nitride precipitation in austenite, it was also observed sigma phase formation near the cells or colonies of discontinuously precipitated chromium nitride. Sigma phase formation was made possible by the depletion of nitrogen in those regions. Time-temperature-transformation (precipitation) diagrams were determined.
Keywords: duplex stainless steel; nitride precipitation; sigma phase precipitation; TTT diagrams